Unraveling the growth mechanism of W18O49 nanowires on W surfaces. Issue 37 (2nd September 2021) - Bandi, Suresh; Srivastav, Ajeet K.
Abstract : This work unravels the solid-state growth mechanism of 1 d W18 O49 nanowires on W surfaces under a water vapor atmosphere. Such growth was understood to be the intermediate WO3 layer formation and its reduction induced planar faults driven 1 d solid-state growth. Abstract : Understanding the growth mechanism is crucial for controlling the morphology and further designing efficient nanostructured materials. Non-stoichiometric tungsten oxides, in particular, W18 O49 nanostructures have shown their prominence for various functional applications. This work presents the growth mechanism of W18 O49 nanowires on W surfaces under H2 O( v ) atmosphere. The phase evolutions are unfolded in view of the detailed thermodynamic considerations. The reaction between W and H2 O( v ) produces WO3 along with H2 as a by-product. H2 acts as a reductant for WO3 and facilitates the W18 O49 phase formation. The complete crystallographic relation of the phase transformation could be represented as W(110)//WO3 (010)//W18 O49 (010). The oxygen vacancy-induced planar defects are responsible for the 1 d [010] growth of W18 O49 NWs. The hexagonal tunnels along the NW length create a passage for H2 O( v ) to repeat the reaction and increase the NW length.